Periprocedural outcome after laparoscopic partial nephrectomy versus radiofrequency ablation for T1 renal tumors: a modified R.E.N.A.L nephrometry score adjusted comparison. (February 2019) - Acosta Ruiz, Vanessa; Ladjevardi, Sam; Brekkan, Einar; Häggman, Michael; Lönnemark, Maria; Wernroth, Lisa; Magnusson, Anders
Background: Comparable oncological outcomes have been seen after surgical nephrectomy and thermal ablation of renal tumors recently. However, periprocedural outcome needs to be assessed for aiding treatment decision. Purpose: To compare efficacy rates and periprocedural outcome (technical success, session time, hospitalization time, and complications) after renal tumor treatment with laparoscopic partial nephrectomy (LPN) or radiofrequency ablation (RFA). Material and Methods: The initial experience with 49 (treated with LPN) and 84 (treated with RFA) consecutive patients for a single renal tumor (diameter ≤ 5 cm, limited to the kidney) during 2007–2014 was evaluated. Patient and tumor characteristics, efficacy rates, and periprocedural outcome were collected retrospectively. The stratified Mantel Haenzel and Van Elteren tests, adjusted for tumor complexity (with the modified R.E.N.A.L nephrometry score [m-RNS]), were used to assess differences in treatment outcomes. Results: Primary efficacy rate was 98% for LPN and 85.7% for RFA; secondary efficacy rate was 93.9% for LPN and 95.2% for RFA; and technical success rate was 87.8% for LPN and 100% for RFA. Median session (m-RNS adjusted P  < 0.001; LPN 215 min, RFA 137 min) and median hospitalization time were longer after LPN (m-RNS adjusted P  < 0.001; LPN 5 days, RFA 2 days). Side effects were uncommon (LPN 2%, RFA 4.8%). Complications were more frequent after LPN (m-RNS adjusted P  < 0.001; LPN 42.9%, RFA 10.7%). Conclusion: Both methods achieved equivalent secondary efficacy rates. RFA included several treatment sessions, but session and hospitalization times were shorter, and complications were less frequent than for LPN. The differences remained after adjustment for renal tumor complexity.